An injectable elastin-based gene delivery platform for dose-dependent modulation of angiogenesis and inflammation for critical limb ischemia. (October 2015) - Dash, Biraja C.; Thomas, Dilip; Monaghan, Michael; Carroll, Oliver; Chen, Xizhe; Woodhouse, Kimberly; O'Brien, Timothy; Pandit, Abhay
Abstract: Critical limb ischemia is a major clinical problem. Despite rigorous treatment regimes, there has been only modest success in reducing the rate of amputations in affected patients. Reduced level of blood flow and enhanced inflammation are the two major pathophysiological changes that occur in the ischemic tissue. The objective of this study was to develop a controlled dual gene delivery system capable of delivering therapeutic plasmid eNOS and IL-10 in a temporal manner. In order to deliver multiple therapeutic genes, an elastin-like polypeptide (ELP) based injectable system was designed. The injectable system was comprised of hollow spheres and an in situ -forming gel scaffold of elastin-like polypeptide capable of carrying gene complexes, with an extended manner release profile. In addition, the ELP based injectable system was used to deliver human eNOS and IL-10 therapeutic genes in vivo . A subcutaneous dose response study showed enhanced blood vessel density in the treatment groups of eNOS (20 μg) and IL-10 (10 μg)/eNOS (20 μg) and reduced inflammation with IL-10 (10 μg) alone. Next, we carried out a hind-limb ischemia model comparing the efficacy of the following interventions; Saline; IL-10, eNOS and IL-10/eNOS. The selected dose of eNOS, exhibited enhanced angiogenesis. IL-10 treatment groups showed reduction in the level of inflammatory cells. Furthermore, we demonstrated that eNOS up-regulated major proangiogenic growth factors such as vascular endothelial growth factors, platelet derived growth factor B, and fibroblast growth factor 1, which may explain the mechanism of this approach. These factors help in formation of a stable vascular network. Thus, ELP injectable system mediating non-viral delivery of human IL10-eNOS is a promising therapy towards treating limb ischemia.